Olfactory Ensheathing Cells Grafted Into the Retina of RCS Rats Suppress Inflammation by Down-Regulating the JAK/STAT Pathway - Xie, Jing; Li, Yijian; Dai, Jiaman; He, Yan; Sun, Dayu; Dai, Chao; Xu, Haiwei; Yin, Zheng Qin (Frontiers in Cellular Neuroscience, 2019)
The inflammatory microenvironment in the retina plays a vital role in the pathogenesis and progression of retinitis pigmentosa (RP). Microglial inflammatory cytokines production leads to gliosis and apoptosis of retinal neurons, and ultimately, visual loss. Cell-based therapies using grafted olfactory ensheathing cells (OECs) have demonstrated modulation of degenerative microenvironments in the central nervous system (CNS), in a number of animal models. However, mechanisms by which grafted OECs can reduce degeneration in the retina are not well understood. In the present study, we set up an in vitro OEC/BV2 microglia co-culture system, and an in vivo Royal College of Surgeons (RCS) rat model, used cell transplantation, immunohistochemistry, RT-PCR, Western Blot to explore the mechanisms by which OECs affect expression of pro- or anti-inflammatory cytokines and polarization of M(IL-6) and M(Arg1) type microglial activation in the retina. We found that compared with the LPS (Lipopolysaccharide) and olfactory nerve fibroblast (ONF), the OEC and BV2 co-culture group modulate microglial cytokines releasing towards the anti-inflammation, and away from the pro-inflammation, which was followed by higher IL-4 and IL-10 and lower IL-6 and TNF-a in their expression levels. In vivo, the transplantation group significantly reduced activated resident microglia/infiltrated macrophage, and expression of pro-inflammatory cytokines in RCS rats retina, increased anti-inflammatory cytokines in transplantation area. Additionally, we found that OECs down-regulated the JAK2/STAT3 (Janus Kinase 2/Signal Transducer and Activator of Transcription 3) pathway. Thirdly, OEC transplantation reduced Caspase-3 expression, protected inner retinal neurons and photoreceptors and therefore, delayed the visual function degeneration. In conclusion, our data suggest that OECs delay retinal degeneration in RP, at least in part through immunomodulation of microglia via the JAK/STAT pathway.